2020
DOI: 10.3892/ol.2020.11457
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated miR‑665 expression independently predicts poor prognosis of lung cancer and facilitates tumor cell proliferation, migration and invasion

Abstract: Non-small cell lung cancer (NSCLC) is one of the leading causes of global cancer-associated mortality. Aberrant microRNAs (miRs) have been reported to be involved in the pathogenesis of various cancer types. The present study aimed to investigate the expression profile and prognostic value of miR-665 in patients with NSCLC, and to analyze its functional role in tumor progression using NSCLC cells. Reverse transcription-quantitative PCR was used to estimate the expression levels of miR-665. Kaplan-Meier surviva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
3
13
0
Order By: Relevance
“…Liu et al also found that miR-665 expression was upregulated in small cell lung cancer tissues (29). Xia et al demonstrated miR-665 up-regulation in NSCLC tissues and cells, with the overexpression of miR-665 promoting cell proliferation, migration, and invasion (30). Likewise, we also found that miR-665 expression was significantly upregulated in LUAD.…”
Section: Discussionsupporting
confidence: 80%
“…Liu et al also found that miR-665 expression was upregulated in small cell lung cancer tissues (29). Xia et al demonstrated miR-665 up-regulation in NSCLC tissues and cells, with the overexpression of miR-665 promoting cell proliferation, migration, and invasion (30). Likewise, we also found that miR-665 expression was significantly upregulated in LUAD.…”
Section: Discussionsupporting
confidence: 80%
“…Nonetheless, miR-665 could facilitate the tumorigenesis of ovarian cancer cells by targeting SRC Kinase Signaling Inhibitor 1 (31). In addition, miR-665 overexpression enhanced the proliferation, migration and invasion of non-small cell lung cancer cells (16). Regarding GC, miR-665 has been documented in several studies to suppress the progression of GC (20,33).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that miRNAs regulate cell proliferation, invasion and apoptosis, as well as serving a pivotal role in tumor progression (14,15). For instance, miR-665 has been associated with lung cancer progression by increasing cell proliferation, migration and invasion (16). Some studies have suggested that miR-665 may be used as a potential molecular target for various types of cancer, including pancreatic (17), breast (18) and ovarian carcinoma (19).…”
Section: Introductionmentioning
confidence: 99%
“…Apart from cardiovascular diseases, microRNAs are also associated with obesity‐associated tumorigenesis. Upregulation of microRNA665 expression independently predicts poor lung cancer prognosis, and promotes tumor cell proliferation, migration and invasion 24 . Wu et al 25 .…”
Section: Discussionmentioning
confidence: 99%